ANALYSIS OF STRENGTHENING THE CHARACTER OF ENTREPRENEURSHIP BASED ON LOCAL WISDOM AT SMA 1 KUDUS - Adella, Vinasya; Kusmuriyanto; Jarot Tri Bowo Santoso (Journal of Economic Education, 2025)
This study aims to analyze and describe in detail the strengthening of the entrepreneurial character based on local wisdom that has been carried out by one of the schools in Kudus Regency, namely SMA 1 Kudus. This type of research is descriptive using qualitative methods. Data collection methods by conducting interviews, observations, and documentation. The data analysis used is an interactive data analysis technique by Miles, Huberman, and Saldana (2014) which consists of data condensation, data presentation, and conclusion drawing or verification. The results of this study show that planning to strengthen the entrepreneurial character based on local wisdom at SMA 1 Kudus is carried out in 3 ways, namely: through Craft and Entrepreneurship learning, through the P5 theme of entrepreneurship, and through the Intra-School Student Organization (OSIS). The implementation is carried out by optimizing the learning process, P5 activities, and student council to prioritize the processing of local natural products from Kudus Regency based on developing local values. Meanwhile, the evaluation of the activity found obstacles, one of which was in fulfilling financial needs during the activity. The conclusion of this research is that SMA 1 Kudus has succeeded in strengthening the entrepreneurial character of students, especially based on local wisdom